PERTANGGUNGJAWABAN PIDANA TERHADAP KORPORASI - P, Santhos Wachjoe (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
The existence of corporation affects the state economy, the society where the corporation stands and the society where the business run. Not only the positive effect but also the negative effect. The corporation was build for some mission and the way it reaches the mission were different one another. It is possible that one or more corporation was build in some way that prohibited by law. For that reason, there is a corporation is involved in various criminal acts or as a means to commit the crimes. Therefore, special attention needs to arrange to snare corporations to take responsibility for an act involving a corporation or as a tool in a criminal offense.Keywords: criminal responsibility, corporation.